The relationship between socioemotional and financial wealth: Re-visiting family firm decision making. (21st November 2016) - Martin, Geoffrey; Gomez-Mejia, Luis
Abstract : Purpose: A growing volume of family firm literature has argued that the preservation of family socioemotional wealth takes precedence over the pursuit of financial goals. The purpose of this paper is to develop a conceptual framework that builds knowledge regarding the two-way relationship between socioemotional and financial forms of wealth, to develop a more complete theory of wealth concerns that may inform family firm decision-making. Design/methodology/approach: The authors conceptually examine contingencies affecting the relationship between financial and socioemotional wealth (in both causal directions). Findings: The authors predict when one form of wealth (socioemotional/financial) is likely to dominate the other (financial/socioemotional) in the family firm's strategic decisions. Originality/value: The paper advances knowledge on the two-way relationship between socioemotional and financial forms of wealth providing a platform for further development in the nascent field of family business research, including our understanding of family firm decisions regarding control and influence over the family business, environmental policy, altruism toward family members, R&D, accounting choices and corporate diversification.